Cardiopulmonary resuscitation on television: are we miseducating the public?. Issue 1108 (9th October 2017) - Colwill, Michael; Somerville, Charlotte; Lindberg, Eric; Williams, Caroline; Bryan, James; Welman, Ted
Abstract: Background: Out-of-hospital cardiac arrest survival rates in the UK are poor, and non-medically trained individuals have been identified to perform substandard cardiopulmonary resuscitation (CPR). Millions watch televised medical dramas and, for many, these comprise their only education on CPR. This study aims to investigate the quality of CPR portrayed on these programmes and whether this has an effect on public knowledge. Methods: Prospective observational study of 30 consecutive episodes of three popular medical dramas. Public knowledge of CPR and viewing habits were assessed with a survey of non-medically trained personnel. Results: 90 episodes were reviewed with 39 resuscitation attempts shown. Chest compression rates varied from 60 to 204 compressions per minute with a median of 122 (95% CI 113 to 132). Depth varied from 1.5 to 7.5 cm with a median of 3 (3.15–4.31). Rate and depth were significantly different from the UK Resuscitation Council Guidelines (2010) (p<0.05, t-test). Survey participants (n=160, 80% response rate) documented what they thought was the correct rate and depth of chest compressions and were scored accordingly. Those who documented watching medical dramas regularly scored significantly worse than those who watched occasionally (p<0.05, Mann-Whitney test). Conclusion: Televised medical dramas depict CPR inaccurately and laypersons may be less well informed about the correct technique the more they tune into these programmes. While there may be other confounding variables, given the popularity of television medical dramas, the poor depiction may be significantly contributing to poor public CPR knowledge and represent a potential new avenue of public education.